2015
DOI: 10.1111/1556-4029.12678
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Chronological Age in Children Under Oncological Treatment

Abstract: The current oncology treatment has improved the survival of children with several types of cancer, and the effect of radiotherapy and/or chemotherapy treatment on dental maturation in comparison with chronological age is not widely known. The aim of this work was to evaluate and compare the impact of radiotherapy and/or chemotherapy treatment during dental maturation with chronological age in Chilean children diagnosed with cancer. Study Design was cross-sectional study on children diagnosed with different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
1
4
0
3
Order By: Relevance
“…Dahllof et al (1994) in a study of 44 cancer patients treated with chemotherapy did not observe any relation between DA and CA when comparing patients with cancer and control group. This is in accordance with previous studies (Flores et al 2015, Vasconcelos et al 2009) where a linear relation between CA and DA was not observed when type of treatment was considered as strata. In the study by Vasconcelos this was attributed to the fact that radiation therapy when applied to ALL patients is not specifically applied to the head and neck region and therefore the effect is not localized.…”
Section: H Eruption Times and Dental Agesupporting
confidence: 93%
See 1 more Smart Citation
“…Dahllof et al (1994) in a study of 44 cancer patients treated with chemotherapy did not observe any relation between DA and CA when comparing patients with cancer and control group. This is in accordance with previous studies (Flores et al 2015, Vasconcelos et al 2009) where a linear relation between CA and DA was not observed when type of treatment was considered as strata. In the study by Vasconcelos this was attributed to the fact that radiation therapy when applied to ALL patients is not specifically applied to the head and neck region and therefore the effect is not localized.…”
Section: H Eruption Times and Dental Agesupporting
confidence: 93%
“…This is in accordance with some (Vasconelos et al 2009) and in contrast with other reports (Dahllof et al 1994, Pajari et al 1988, Khojastepour et al 2014. In a study by Flores et al (2015) in a group of childhood cancer survivors a highly significant correlation was reported between CA and DA and similarly in a study by Vasconcelos et al a significantly advanced DA was reported in ALL patients when compared to control group. Ozerovic et al (1980) reported a difference in DA and CA that ranged between 1 and 7 months in a group of children with cerebral palsy.…”
Section: Dental Agementioning
confidence: 58%
“…Bu nedenle kemoterapi ve radyoterapi uygulaması süresince dental tedavilerin yapılması, hem dental komplikasyonların önlenebilmesi, hem de tedavi protokolünün aksamaması için oldukça önemlidir. [13][14][15][16][17] Aynı şekilde ailelere dental gelişimin uzun dönemde de etkilenebileceği, ortodontik problemler ortaya çıkabileceği belirtilmelidir. [18][19][20][21] Bu amaçla çocukluk çağı kanser teşhisi konulduğu andan itibaren çocukların diş hekimine düzenli kontrol için gitmeleri konusunda aileler teşvik edilmelidir.…”
Section: Discussionunclassified
“…Bu çalışmalarla benzer olarak çocukların %85'i 5yaşın altında ALL tanısı almıştır. 14,15 Çalışmamızda ALL ve kontrol grubunda dental ve kronolojik yaşlar kıyaslandığında, ALL'li çocukların ortalama dental yaşı, ortalama kronolojik yaştan istatistiksel olarak anlamlı olarak yüksek bulunurken, kontrol grubunda dental yaş ve kronolojik yaş ortalamaları arasında bir fark bulunmamıştır. Pajari ve ark 32 , radyoterapi ile kombine veya sadece kemoterapi alan 38 çocukta aynı metodu kullanarak dental gelişimi inceledikleri çalışmalarında sonuçlarımızla benzer olarak tedavi gören çocukların dental yaşının kontrol grubuna göre daha fazla olduğu bulmuşlar, ancak aradaki farkın istatistiksel olarak çok anlamlı olmadığını belirtmişlerdir.…”
Section: Bulgularunclassified
“…[6][7][8][9][10][11][12][13] Ancak ALL tedavisinin dental yaş üzerine etkisiyle ilgili araştırmaların az olması nedeniyle kesin sonuçlar elde edilememiştir. [14][15][16][17] Bu çalışmanın amacı, radyoterapi ile kombine veya sadece kemoterapi içeren tedavi ALL protokollerinin çocukların dental yaşı üzerine etkisini incelemektir.…”
Section: Introductionunclassified